Peningkatan Teknik Pembuatan Pupuk Organik Majemuk pada Kelompok Kaum Bapak Jemaat GMIT Mizpa Bonen, Kecamatan Taebenu Kabupaten Kupang - Pollo, Roddialek; Benggu, Yoke I.; Adu Tae, Anthonius S. J.; Widinugraheni, Sri; Taloim, Aristarkhus; Imanuel Nalle, Ryan Pieter (Universitas Pahlawan Tuanku Tambusai, 2025)
This service activity has been carried out in the GMIT Mizpa Bonen categorical group, most of whom work as farmers and livestock breeders who are members of the dry land farmer group. The aim of this training is to provide knowledge, understanding and skills about increasing productivity through the use of livestock manure, dry land weeds and plant litter as compound organic fertilizer which has higher economic value and plays a dual role in dry land plant cultivation. The approach method for this activity is lectures and direct practice regarding the application of making compound organic fertilizer. The results achieved from this PKM activity are that the community has increased knowledge and skills in utilizing plant biomass around their living environment as organic fertilizer to support the growth and development of cultivated plants.